The Blindness of Mortals. The Philosopher: between Human Jest and Divine Envy - Posada González, María Cecilia (Estudios de Filosofía, 2006)
The first Philosophers were very conscious of the novelty that they introduced in the way they related to the World, which is, a change in perspective that distanced from the dose and the immediate, to approach everything contemplatively. From the predominance that vision had in the Greek tongue came terms and metaphors as the blindness of mortal people, which not only illustrate the contrast between the daily way of life and the philosophical one, but which dramatize it as the old anecdote on Thales. Why, both yesterday and today, is the Philosopher laughablefor the majority, while, he considers himself object of the envy o f the gods?